FUCIK SPECTRUM FOR A THIRD ORDER BOUNDARY VALUE PROBLEM - Rojas Romero, Santiago César (2011)
In this work, the Fucik Spectrum for the boundary value problemis studied, and the Fucik curves contained in this spectrum are described.